2014
DOI: 10.1051/0004-6361/201424054
|View full text |Cite
|
Sign up to set email alerts
|

AHerschel[C II] Galactic plane survey

Abstract: Context. The [C ii] 158 μm line is the brightest far-infrared cooling line in galaxies, representing 0.1 to 1% of their far-infrared continuum emission, and is therefore a potentially powerful tracer of star formation activity. The [C ii] line traces different phases of the interstellar medium (ISM), including the diffuse ionized medium, warm and cold atomic clouds, clouds in transition from atomic to molecular, and dense and warm photon dominated regions (PDRs). Therefore without being able to separate the co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
138
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(145 citation statements)
references
References 82 publications
(143 reference statements)
7
138
0
Order By: Relevance
“…Such observations have shown that while XF can be more or less spatially constant in some cases, like in the disk of our Galaxy and other external galaxies (see Sandstrom et al 2013;Planck Collaboration 2011a), there can be regions of "dark" gas, H2 with no CO emission, both in our Galaxy and other galaxies (e.g., see Planck Collaboration 2011a; Baes et al 2014;Clark et al 2012;Pineda et al 2014;Roman-Duval et al 2010;Saintonge et al 2012;Smith et al 2014). Therefore, observations of dust continuum emission provide a vital check on results inferred from CO J = 1 → 0 observations.…”
Section: Introductionmentioning
confidence: 84%
“…Such observations have shown that while XF can be more or less spatially constant in some cases, like in the disk of our Galaxy and other external galaxies (see Sandstrom et al 2013;Planck Collaboration 2011a), there can be regions of "dark" gas, H2 with no CO emission, both in our Galaxy and other galaxies (e.g., see Planck Collaboration 2011a; Baes et al 2014;Clark et al 2012;Pineda et al 2014;Roman-Duval et al 2010;Saintonge et al 2012;Smith et al 2014). Therefore, observations of dust continuum emission provide a vital check on results inferred from CO J = 1 → 0 observations.…”
Section: Introductionmentioning
confidence: 84%
“…Based on numerical models of photo-ionization gas and PDRs using the Cloudy model (Ferland et al 2013), Abel (2006) presented the following correlation, This is a much higher fraction than the often assumed range of 10−60% (Abel 2006). Pineda et al (2014) estimate that in the Milky way the contribution from different gas phases to the [C II] luminosity is dense PDRs (30%), cold HI (25%), CO-dark H 2 (25%), and ionized gas (20%). These are averaged values.…”
Section: [N Ii] and [C Ii] Analysismentioning
confidence: 99%
“…On global scales, [C II] emission from H II regions only contributes about 20% to the total [C II] intensity (Pineda et al 2014), but an increased active star formation gives rise to a higher FUV flux on larger scales and to an enhanced [C II]/CO line ratio accordingly. The much higher angular resolution of the SOFIA [C II] data compared to the data available to Stacey et al (1991) reveals significant local variations in the line ratio when pointing on or off sites of active star formation.…”
Section: The [C Ii] To 12 Co (1−0) Ratiomentioning
confidence: 99%
“…The fine structure line of ionized carbon, [C ii], at 158 μm is widely used to trace the galactic star formation rate (SFR; Stacey et al 2010;de Looze et al 2011de Looze et al , 2014Pineda et al 2014), as is the far-infrared (FIR) dust emission (e.g. Malhotra et al 1997;Luhman et al 1998;Stacey et al 2010;de Looze et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However there are some notable exceptions in which the luminosity of [C ii] is significantly suppressed with respect to the infrared luminosity. The relationship between the intensity of [C ii] and other star formation tracers appears to work in the Galactic disk (Pineda et al 2014) and most extragalactic sources (de Looze et al 2014), however it breaks down somewhat in many luminous infrared galaxies (LIRGs; Díaz-Santos et al 2014) and ultra luminous infrared galaxies (ULIRGs; Malhotra et al 1997;Luhman et al 1998;Rigopoulou et al 2014) and even more so in many active galactic nuclei (AGN; Stacey et al 2010, Sargsyan et al 2014, Gullberg et al 2015. The assumption is that there is a deficit in [C ii] luminosity in these sources and in particular in their central regions (Malhotra et al 1997;Luhman et al 1998;Rigopoulou et al 2014;Gullberg et al 2015).…”
Section: Introductionmentioning
confidence: 99%